2020
DOI: 10.24843/jsgs.2020.v04.i01.p03
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Level of Knowledge in Preventing Coronary Heart Disease Among Community Sample

Abstract: CHD is ranked number one as a cause of death in non-communicable diseases in Indonesia. The increasing number of people with CHD not only having an impact on mortality rates also an increase in health care needs. Adequate knowledge of the disease contributes to an accurate understanding of the disease and improves adherence to a healthy lifestyle to prevent CHD. This study aims to analyze the awareness and level of community knowledge in preventing CHD. This research was a quantitative research with descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 7 publications
1
8
2
2
Order By: Relevance
“…Knowledge of risk factors that are commonly known by the study participants was smoking (94.2%) followed by physical activity (90.9%) and overweight (86.9%). These results were in harmony with the previous studies that reported that the level of knowledge on smoking risk factors received the highest score (90.3% and 89.1%) (Fahs et al, 2017; Suarningsih & Suindrayasa, 2020). Family history of CVD, dyslipidemia, hypertension, and diabetes was less frequently identified by participants as risk factors for developing CVDs.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Knowledge of risk factors that are commonly known by the study participants was smoking (94.2%) followed by physical activity (90.9%) and overweight (86.9%). These results were in harmony with the previous studies that reported that the level of knowledge on smoking risk factors received the highest score (90.3% and 89.1%) (Fahs et al, 2017; Suarningsih & Suindrayasa, 2020). Family history of CVD, dyslipidemia, hypertension, and diabetes was less frequently identified by participants as risk factors for developing CVDs.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies conducted in Saudi Arabia supported the findings that there is limited knowledge about the CVDs risk factors among the Saudis in Jeddah (Almalki et al, 2019), Qassim (Albadrani et al, 2020), Riyadh (Mujamammi et al, 2020), and Western region (Alghamdi et al, 2021). This is higher than what was obtained in India (60.26 ± 17.20) (Yeluri et al, 2021), and lower than a study conducted in Indonesia (Suarningsih & Suindrayasa, 2020). In comparison with another study conducted among university teachers in Saudi Arabia, the mean knowledge scores were higher ranges from 72.97% to 74.31% (Tomar et al, 2015).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations